2001
DOI: 10.1046/j.1524-4733.2001.40202-219.x
|View full text |Cite
|
Sign up to set email alerts
|

Pmh33: Olanzapine Versus Risperidone in the Treatment of Schizophrenia: A Comparison of Costs Among Texas Medicaid Patients

Abstract: OBJECTIVE: The purpose of this retrospective study is to examine both schizophrenia‐related direct costs and total (schizophrenia plus non‐schizophrenia) direct costs among Texas Medicaid patients who have been diagnosed with a schizophrenic disorder and have been initiated on one of two atypical antipsychotics (olanzapine or risperidone). METHODS: Services and prescription utilization and cost data were retrieved for 3,072 patients with schizophrenia who were initiated on olanzapine or risperidone between 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 0 publications
8
32
1
Order By: Relevance
“…15 Although our study included home health care costs and inpatient costs, it did not include nursing home costs, which could explain the negative relationship found between age and costs. A similar negative relationship between age and schizophrenia-related costs was also observed by Rascati et al (2003). 17 Patients with a spouse or those under age 16 had significantly lower schizophrenia-related expenditures compared with those without a spouse.…”
Section: ■■ Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…15 Although our study included home health care costs and inpatient costs, it did not include nursing home costs, which could explain the negative relationship found between age and costs. A similar negative relationship between age and schizophrenia-related costs was also observed by Rascati et al (2003). 17 Patients with a spouse or those under age 16 had significantly lower schizophrenia-related expenditures compared with those without a spouse.…”
Section: ■■ Discussionsupporting
confidence: 56%
“…[14][15][16][17] The prevalence of schizophrenia varies by age, gender, race, insurance status, family income as a percentage of poverty line, and marital status. 3,18 Thus, we also expected the costs to vary by these factors.…”
Section: Identifying Patient Characteristics Associated With High Schmentioning
confidence: 99%
“…In the United States, olanzapine initiators were found to have more complex psychiatric histories than risperidone initiators including more pre-existing psychiatric comorbidities [20], more prior use of other classes of psychiatric medications [20,21], higher prior psychiatric inpatient costs [22], more previous treatment with clozapine [21,23,24], and more initial prescriptions from psychiatrists [24]. Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use.…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with these prior studies, olanzapine initiators in the current analysis were more likely to have diagnoses for manic episodes and had more prior antidepressant use. In the United States, risperidone was found to be initiated more often than olanzapine for patients with schizophrenia who have more physical comorbidities [20,[22][23][24][25]. Consistent with these studies, the univariate analysis found that risperidone initiators were more likely to have previous claims for diabetes mellitus.…”
Section: Discussionmentioning
confidence: 53%
“…There is a rule of thumb that if the F-statistic value is greater than 10, the first assumption holds [13,96,97]. Other measures for the strength of the association between IVand exposure include the first-stage regression coefficient of the IV [50,98] or the R 2 of a linear first-stage model [15,78,83], the odds ratio [6,93], or pseudo-R-squared of the first-stage model [76]. When the correlation between IVand exposure is not strong enough, IVanalysis is likely to be biased (weak IV bias, which increases with the weakness of the IV).…”
Section: Assessment Of Ivassumptionsmentioning
confidence: 99%